Application of diosmin at intrahepatic portal hypertension - G. K. Mirodzhov; S. A. Avezov; M. M. Giyasov; S. G. Mirodzhova (Российский журнал гастроэнтерологии, гепатологии, колопроктологии)
Aim of investigation. To study efficacy of phlebodia-600 (diosmin) in treatment of portal hypertension at patients with liver cirrhosis (LC).Methods. Comparative investigation of efficacy of monotherapy by enalapril (10 mg/day) and phlebodia600 (1200 mg/day), and their combination at portal hypertension has been carried out at 35 patients with LC of Child-Pugh classes A and B.Results. Phlebodia-600 more significantly, than enalapril, decreased diameter of portal and splenic veins, but had no essential effect on peripheral blood flow velocity. Combined treatment by these agents along with decrease of diameter of veins significantly increased average rate of blood flow in portal vein and decreased splenic venous blood flow. The average value of congestive index in portal vein at monotherapy by enalapril decreased by 30,5%, at application of phlebodia-600 – by 26,0%, at their combined application – by 51,4%. The combined treatment significantly decreased hepatic artery resistance index (by 25%) as well.Conclusion. Combined application of enalapril and phlebodia-600 in the treatment of portal hypertension is more effective, than monotherapy.